Closing the crop yield gap between organic and conventional farming systems in Kenya: long-term trial research indicates agronomic viability - Bautze, D.; Karanja, E.; Musyoka, M.; Ruegg, J.; Goldmann, E.; Kiboi, M.; Kampermann, I.; Cotter, M.; Riar, A.; Matheri, F.; Mwangi, E.; Mucheru-Muna, M.; et al. (Elsevier, 2024)
The production gap between current and attainable yields is highest on Africa`s smallholder farms, and some studies indicate that they might not benefit from the yield gains offered by conventional farming. Simultaneously, alternative farming systems like organic provide biodiversity and soil fertility advantages, but their ability to produce sufficient food is still under debate. Additionally, comparative data on the productivity of organic versus conventional in tropical regions are scarce or short-term. We investigated the crop productivity of organic and conventional farming systems using 15 years in two long-term systems comparison trials in Kenya. The trials were established in 2007 at two sites in the Central Highlands of Kenya. At each site, conventional and organic systems were compared at high input levels. The trial involved a three-year crop rotation cycle of maize, vegetables, legumes, and potatoes, repeated five times since its establishment. Management practices were kept similar in the first four rotations and revised in the fifth to improve systems representing best practices. Our results showed that while maize and baby corn had relatively low yield gaps (-13 to +12%) between organic and conventional systems, cabbage, French beans, and potato had high yield gaps (-50 to -30%). We attributed this to nutrient limitations and higher pest and disease damage. The yield gap could partially be closed by adopting best practices in the organic system, including system diversification and effective soil fertility, nutrient, and integrated pest management.